2017
DOI: 10.1007/s00431-017-3022-9
|View full text |Cite
|
Sign up to set email alerts
|

There is no association between vitamin D status and characteristics of central precocious puberty in girls

Abstract: Overall, our patients had a satisfactory vitamin D status. We did not find any correlation between vitamin D status and the characteristics of central precocious puberty. Further studies are required to confirm this hypothesis. What is known: • Vitamin D status seems to affect gonadal hormones and fertility. • Vitamin D deficiency may contribute to earlier puberty and was associated with earlier menarche. What is new: • 25OHD of 145 girls with precocious puberty was similar to or higher than that of healthy Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…In addition, one study demonstrated an inverse association between BMI and WHR with serum vitamin D levels (15). However, our results demonstrated no correlation between vitamin D and either BMI or WHR in the women with PCOS; this may be related to the large heterogeneity with regard to vitamin D levels in relation to small sample size, the use of BMI to indicate adiposity, the small number (6) of women with vitamin D deficiency in the PCOS group, and methodological differences in measuring vitamin D. In line with these findings, in a few studies in which BMI was measured, no association with vitamin D deficiency in young patients with PCOS was reported (34,35). A study that used dual-energy X-ray absorptiometry (DEXA) to measure fat mass, abdominal fat mass, and fat-free mass in patients with PCOS and measured the correlation of BMI with vitamin D; reported that although their PCOS and control groups had similar adiposity levels, vitamin D levels were lower in the PCOS group (36).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, one study demonstrated an inverse association between BMI and WHR with serum vitamin D levels (15). However, our results demonstrated no correlation between vitamin D and either BMI or WHR in the women with PCOS; this may be related to the large heterogeneity with regard to vitamin D levels in relation to small sample size, the use of BMI to indicate adiposity, the small number (6) of women with vitamin D deficiency in the PCOS group, and methodological differences in measuring vitamin D. In line with these findings, in a few studies in which BMI was measured, no association with vitamin D deficiency in young patients with PCOS was reported (34,35). A study that used dual-energy X-ray absorptiometry (DEXA) to measure fat mass, abdominal fat mass, and fat-free mass in patients with PCOS and measured the correlation of BMI with vitamin D; reported that although their PCOS and control groups had similar adiposity levels, vitamin D levels were lower in the PCOS group (36).…”
Section: Discussionmentioning
confidence: 93%
“…In the PCOS patients Vit D correlated negatively with FSH, but the correlation was not statistically significant (38). In an earlier study Zolkova et al (39) had shown that there was an improvement in FSH level with specific doses of Vit D. However, a recent report failed to show any correlation between Vit D and FSH and LH in young females (40).…”
Section: Discussionmentioning
confidence: 96%
“…D and BMI, though earlier investigations showed that Vit D associates with BMI (10, 11, 13). Recently, Duhil de Benaze (40) also failed to show any association between Vit D and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, there was su cient homogeneity in the seasonal distribution among the participants included in this study (CPP and control groups). However, previous studies that evaluated a possible association between vitamin D status and timing of puberty in girls have several limitations, since they either did not refer to race or season of the year in which the sample was collected [12][13][14], or did not include a group control [15]. In other words, this study allows us to analyze the results obtained avoiding confounding factors.…”
Section: Discussionmentioning
confidence: 99%